FREQUENCY OF TYPE 2 DIABETES MELLITUS IN PATIENTS WITH CHRONIC HEPATITIS C VIRUS INFECTION - Sumera Riaz; Muhammad Siddique Khan Qadri; Khurram Sohail et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT:BACKGROUND: In developing countries, Diabetes Mellitus and Hepatitis C virus infection are major public health problems. A range of extra-hepatic manifestation such as artharlgia, thyroiditis and Type 2 Diabetes Mellitus are associated with Hepatitis C virus infection. Almost one-third of the patients suffering from Chronic Hepatitis C virus infection develop Type 2 Diabetes Mellitus.OBJECTIVE: 1 To study the prevalence of Type 2 Diabetes Mellitus in Chronic Hepatitis C virus patients. METHODOLOGY: A case-control study was conducted from June 2014 to Dec 2014 at Madinah Teaching Hospital. A non-probability convenient sampling technique was used, after approval from hospital ethical committee. Participants with evidence of chronic Hepatitis C virus infection, in form of positive ELISA, positive PCR for HCV RNA with raised serum ALT, were evaluated for presence of Type 2 Diabetes Mellitus. Clinical and ultrasonographic evidence of cirrhosis in these participants were also checked. These participants (cases) were then compared with healthy blood donors (controls) visiting blood donation centre in Madinah Teaching Hospital, for Hepatitis C virus infection and presence of Type 2 Diabetes Mellitus.RESULTS: 242 participants suffering from Chronic Hepatitis C infection were inducted. Out of these 242, 53% (n= 128) were male and 47% (n= 114) were females, with male to female ratio 1.2: 1. Type 2 Diabetes Mellitus was present in 27% (n= 66) of the participants. Maximum number 75.5% (n= 183) diabetic patients were in age group of > 40 years. In our study genotype 3 was most prevalent, 83% (n= 201), followed by genotype 1, in 11% (n=27) of participants. Healthy donors were considered as control group. Out of these controls (n=242), only 3.3% (n= 8) were positive for Hepatitis C virus infection. In these 3% only one person was found to diabetic according to WHO criteria.CONCLUSION: The prevalence of Diabetes Mellitus in patients with Chronic Hepatitis C infection is higher than in the general population. This prevalence is even higher in healthy blood donors with Hepatitis C, emphasizing that only presence of Hepatitis C virus is not sufﬁcient to produce the Type 2 Diabetes Mellitus but it is the presence of Chronic Hepatitis C which is fundamental.